2008
DOI: 10.1007/s11814-008-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of packing materials in biofilter system for the biological removal of hydrogen sulfide: Polypropylene fibrils and volcanic stone

Abstract: In order to develop a method for the removal of hydrogen sulfide via a biological process, two different packing materials were tested to assess their capabilities as biofilter bed materials under variable conditions of two parameters: inlet gas concentration and inlet gas flow rate. We detected a maximal elimination capacity (critical loading rate) of 515.1 (410.5) g-H 2 S/m 3 ·hr, and 415.5 (80.0) g-H 2 S/m 3 ·hr, respectively, when polypropylene fibrils and volcanic stone were employed as supporting materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Chung et al (2004) and Ng et al (2004) found that the biofilter in which the activated carbon composite was utilized as a packing material, evidenced a stable removal yield over 92 per cent at high inlet H 2 S concentration. In the case of polymer packing, the removal efficiency achieved is more than 90 percent (Hirai et al, 1990;Koe and Yang, 2000;Aroca et al, 2007;Jeong et al, 2008;Potivichayanon et al, 2006) even at low EBRT. Other packings, namely coconut coir pitch, saw dust, rice husk, and sugarcane bagasse showed low removal efficiency of H 2 S (Potumarthi et al, 2009).…”
Section: -150mentioning
confidence: 96%
See 1 more Smart Citation
“…Chung et al (2004) and Ng et al (2004) found that the biofilter in which the activated carbon composite was utilized as a packing material, evidenced a stable removal yield over 92 per cent at high inlet H 2 S concentration. In the case of polymer packing, the removal efficiency achieved is more than 90 percent (Hirai et al, 1990;Koe and Yang, 2000;Aroca et al, 2007;Jeong et al, 2008;Potivichayanon et al, 2006) even at low EBRT. Other packings, namely coconut coir pitch, saw dust, rice husk, and sugarcane bagasse showed low removal efficiency of H 2 S (Potumarthi et al, 2009).…”
Section: -150mentioning
confidence: 96%
“…Amongst them polymer packings (Hirai et al, 1990;Ruokojarvi et al, 2000;Aroca et al, 2007;Jeong et al, 2008;Ramírez et al, 2009;Ng et al, 2004;Potivichayanon et al, 2006), activated carbon (Chung et al, 2004 ;Ng et al, 2004), volcanic stone (Lee et al, 2001;Jeong et al, 2008), ceramics (Shinabe et al, 1995;Ruokojarvi et al, 2000), calcium alginate beads (Chung et al, 1997), coconut coir pitch, saw dust, rice husk, and sugarcane bagasse (Potumarthi et al, 2009) are important ones. Jeong et al (2008) compared two different packing materials (polypropylene fibrils and volcanic stone) for the H 2 S removal. They detected a maximum elimination capacity of 515 g H 2 S.m -3 .h -1 and 415 g H 2 S.m -3 .h -1 on polypropylene fibrils and volcanic stone respectively.…”
Section: -150mentioning
confidence: 99%
“…In the first stage, the performance of the filters was evaluated during the start-up period at a constant empty bed residence time (EBRT) of 60 seconds and different inlet concentrations of H 2 S ranging from 10 to 300 ppm. According to the study by Jeong et al in order to adapt the microorganisms in the filters, the tested H 2 S gas was introduced in the filters at low concentration of 10 ppm for one week (6). After the adaptation period, H 2 S concentration at the inlet was increased in weekly increments.…”
Section: Operation Of the Systemmentioning
confidence: 99%
“…In particular, inhalation of low concentrations of hydrogen sulfide can cause headache, dizziness, nausea, cramps, staggering, excitability, and drowsiness. In actual situations such as industrial emissions, the strong odor threshold and vapor density cause them to travel several kilometers from the emission site (6). In order to solve environmental problems more effectively, researchers need to focus on design and optimization of the treatment processes for environmental pollution (7).…”
Section: Introductionmentioning
confidence: 99%
“…Such media are important in drying systems, as described by Amanifard and Haghi [6], fluid-separation technologies, as studied by Kim and Chung [7], processes involving superposed porous saturated media and fluid layers, as elaborated by Kim et al [8], and hydrogen sulfide biofiltration systems as discussed by Jeong et al [9]. Yim et al [10] have studied porous media flows in the context of cake filtration including pre-sedimentation effects using the Ruth equation.…”
Section: Introductionmentioning
confidence: 99%